Responses of the Stock Market to Macroeconomic Announcements Across Economic States - Hu, Zuliu (IMF Working Papers; Working Paper ;, 1998)
Is the stock market responsive to macroeconomic news? This paper employs the daily returns of the Dow Jones Industrial Index, the S and P 500 index, the Russell 1000 index, and the Russell 2000 index to examine stock market reactions to a broad list of macroeconomic announcements, including money supply, inflation, employment, housing starts, and trade balances, et cetera Several announcements concerning real economic activity that have received little attention in previous research are shown to have a significant impact on stock prices. The paper also presents preliminary evidence for the different reaction to macroeconomic news by small cap stocks and large cap stocks.